3x-4y=5

2x-5y=-3

3x - 4y = 5 ----(1)

2x - 5y = -3 ----(2)

Multiply equation (1) by 2

6x - 8y = 10 ---(3)

Multiply equation (2) by 3

6x - 15y = -9 ---(4)

Subtract equation (4) from equation (3) to eliminate x

6x - 8y - (6x - 15y) = 10 - (-9)

6x - 8y - 6x + 15y = 10 + 9

7y = 19

y = 19/7 = 2.7

Substitute value of y in equation (1)

3x - 4*2.7 = 5

3x - 10.8 = 5

3x = 10.8 + 5

3x = 15.8

x = 15.8/3

x = 5.3

So, solution = (5.3, 2.7)

ANSWER: (5.3, 2.7)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up